Localized nutrient colimitation of phytoplankton growth rates across the subtropical South Pacific Ocean - Zhongwei Yuan; Haoran Liu; Kathleen J. Gosnell; Zuozhu Wen; Anja Engel; Minhan Dai; Eric P. Achterberg; Thomas J. Browning (Proceedings of the National Academy of Sciences, 2025)
The simultaneous depletion of multiple nutrients in seawater potentially leads to colimitation of phytoplankton growth across large oceanic extents. Single limitation versus colimitation carries implications for mathematically predicting growth, its response to environmental forcing, and evaluating biogeochemical feedbacks. However, identifying colimited growth has proved challenging due to a lack of appropriate methods. Here, we present the results of 12 experiments conducted across the South Pacific that used a matrix of nutrient additions to strongly diluted surface seawater. Dilution restricted both grazing rates and nutrient drawdown due to phytoplankton accumulation. We find that despite simultaneous depletion of nitrate, phosphate, and iron concentrations throughout the oligotrophic gyre, community-level phytoplankton growth rates were only constrained by nitrogen. In contrast, zones of colimitation and serial limitation by nitrogen and iron were found along the eastern gyre margin. At the nitrogen-iron co-/serially limited sites, growth response surfaces to nutrient additions varied, suggesting the need for dynamic models to accurately represent colimited phytoplankton growth in the ocean.